Unlocking the Complete Chloroplast Genome of a Native Tree Species from the Amazon Basin, Capirona (Calycophyllum spruceanum Benth., Rubiaceae), and Its Comparative Analysis with Other Ixoroideae Species - Saldaña Serrano, Carla Lizet; Rodriguez Grados, Pedro; Chávez Galarza, Julio César; Feijoo Narvasta, Shefferson; Guerrero Abad, Juan Carlos; Maicelo Quintana, Jorge Luis; Jhoncon, Jorge H.; Arbizu Berrocal, Carlos Irvin (MDPI, 2021)
16 páginas